PROFESSIONAL DEVELOPMENT IN OPEN AND DISTANCE LEARNING SYSTEM: ANALYTICAL EVALUATION OF TRAINING PROGRAMMES - Dimri, Anil K.; Misra, Anil Kumar (AAOU journal, 2008)
Present article seeks to analyze the impact of training programmes on the professional development skills of the academics working primarily at the Regional Centers of Indira Gandhi National Open University spread across the country. Article also seeks to analyze how the issues pertaining to the academics which include educational, administration, student support, supervision and maintenance of study centers. monitoring, staff development, survey and research activities, development of self instructional material, admission, examination, teleconferencing, interactive radio counseling, gyanvani, tele-learning center activities, maintenance of database, financial and administrative matters were taken up while imparting training. Interrelationship among the variables was also analyzed in order to asses the impact one variable on the other variables by using regression technique, i.e while dealing with the issues pertaining to educational administration the impact of training on monitoring was also assessed.